Potential RNA polymerase II-induced interactions of transcription factor TFIIB. - Malik, S (1993)
The ubiquitous transcription factor TFIIB is required for initiation by RNA polymerase II and serves as a target of some regulatory factors. The carboxy-terminal portion of TFIIB contains a large imperfect direct repeat reminiscent of the structural organization of the TATA-binding component (TBP) of TFIID, as well as sequence homology to conserved regions of bacterial sigma factors. The present study shows that the carboxy-terminal portion of TFIIB, like that of TBP, is folded into a compact protease-resistant core. The TFIIB core, unlike the TBP core, is inactive in transcription but retains structural features that enable it to form a complex with promoter-bound TFIID. The protease-susceptible amino terminus appears to contain components responsible for direct interaction with RNA polymerase II (in association with TFIIF) either on the promoter (in association with TFIID) or independently. In addition, core TFIIB (but not intact TFIIB) extends the footprint of TBP on promoter DNA, suggesting that TFIIB has a cryptic DNA-binding potential. These results are consistent with a model in which TFIIB, in a manner functionally analogous to that of bacterial sigma factors, undergoes an RNA polymerase II-dependent conformational change with resultant DNA interactions during the pathway leading to a functional preinitiation complex.